Biodiesel - Feedstocks, Production and Applications 2012
DOI: 10.5772/52157
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Detoxification of Jatropha Seed Cake and Its Use in Animal Feed

Abstract: compound formed during seed maturation [12]. The seed of J. curcas has a high concentration of phytic acid, up to 10% of its dry matter [2]. Tannins are polyphenols water-soluble and polar solvents [13]. The tannin content in the seeds of J. curcas is low, representing only 3% of its dry weight [13].Detoxification of the Jatropha seed cake could allow its use as a protein-rich dietary supplement in the animal feed [1,14,15].The use of residue or by-products in animal nutrition can minimize expenditures on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
0
7
2
Order By: Relevance
“…The above authors pointed out that consumption and palatability of the feed was not diminished by the inclusion of detoxified Jc. Here, lignin and cellulose/hemicellulose content after fungal growth (Table 1) were lower than that reported by Kasuya et al (2012). In this study, Jc supplemented with 10% coffee husk and processed via fungal growth showed good potential for use as an animal feed.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…The above authors pointed out that consumption and palatability of the feed was not diminished by the inclusion of detoxified Jc. Here, lignin and cellulose/hemicellulose content after fungal growth (Table 1) were lower than that reported by Kasuya et al (2012). In this study, Jc supplemented with 10% coffee husk and processed via fungal growth showed good potential for use as an animal feed.…”
Section: Discussioncontrasting
confidence: 54%
“…Recently, P. ostreatus growth in Jc was observed to increase its in vitro digestibility and the amount of nonfiber carbohydrates and crude protein (da Luz et al, 2014), which are all desirable features for animal feed (Montagne et al, 2003). Moreover, Kasuya et al (2012) showed that Jc after P. ostreatus growth was well-accepted by goats, leading to an increase in dry mass intake. The above authors pointed out that consumption and palatability of the feed was not diminished by the inclusion of detoxified Jc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All fungi treated biomasses presented high-rate degradation (except for those with S. commune) reaching permissible levels for ruminant's feed. Signi cant reduction in FG content was also reported from other authors [24] working with Pleurotus sp., with degradation percentages reaching 100% [51]. In addition, some authors analyzing 06 basidiomycetes including P. lecomtei, F. hepatica, Ganoderma sp., and Pleurotus sp.…”
Section: Discussionmentioning
confidence: 99%